Analysis of indicators of economic efficiency of meat and dairy products production - Abdullaev Jasur Abdijabborovich (THE INNOVATION ECONOMY, 2026)
The article analyzes the factors influencing the economic efficiency of dairy and meat production and ways to improve its efficiency. The level of provision of farmers and cattle breeders of the Republic of Uzbekistan, including the Kashkadarya region, with dairy and meat products, as well as the directions of providing the population with livestock products are disclosed.